Vinca alkaloids effects on the morphological characters of Canavalia ensiformis - Putri, Diah Asta; Rahyuni, Mita; Sarwati, Mega (Journal of Biotechnology and Natural Science, 2022)
Productivity and quality of crops can be increased through polyploidy plants induced by antimitotic compounds such as vinka alkaloids.The use of vinka alkaloids has never been applied to Sword bean (Canavalia ensiformis), a tropical legume belonging to the Fabaceae family. This study aimed to determine the effects of vinka alkaloids treatment on the morphological characters of Sword bean. The treatment consist of four different vinka alkaloids concentrations (0.5%, 1.00%, 1.50%, 2.0%, and untreated (0.0%) act as control. The plants were arranged in a completely randomized design. Treated plants were characterized based on morphological traits such as plant height, leaf area and dry seed weight. The results obtained revealed significant difference (p≤0.05) in the morphological traits of the treated plants when compared with the control. Overall, 2.0% vinka alkaloids concentration resulted in higher average plant height by 193.8 ± 1.86, leaf area increments by 88.6 ± 5.1 (left leaf), 115.1 ± 4.7 (middle leaf), 86.2 ± 3.8 (right leaf) and the dry seed weight by 1.7 ± 3.6. The improvement of the traits is concentration dependent and increases with increment in vinka alkaloids concentration. Thus, we suggested that 2.0% concentration should be employed in improving Sword bean growth and yield.